O caráter multifacetado da pobreza : a relação entre concepção e intervenção - Williams, Ava Renarda (2007)
This research analyzes the multifaceted and complex nature of poverty. The principle objective of this research is the comprehension of the multideterminants which comprise poverty as well as the influence that the manner in which poverty is conceived exerts upon the development and implementation of strategies geared toward alleviating poverty. This work utilizes a bibliographical framework that explores the historical trajectory of poverty contemplating its transformation throughout various historical periods (i.e Middle Ages, Modernity and Post-Modernity). The concepts of poverty utilized in this research explore the analyses of a plethora of authors, reflecting a large degree of diversity in the criteria considered explicative of the concepts, determinants and causes of poverty. This research also highlights the necessity of considering the poor in their positive concreteness , or rather, considering the experiences, representations and survival strategies of the poor in a positive, rather than negative context, in order to reinforce their potential and capacity to contribute to efforts geared toward alleviating poverty. The results of this research indicate that the manner in which poverty is perceived influences the formation of politics and policies geared toward its combat, the relationship established between professionals (i.e. social workers, politicians, etc.) and the poor populations with which they interact as well as the development and implantation of strategies geared toward alleviating poverty. If the poor are viewed as individuals capable of improving their reality, the programs and policies adopted emphasize their potential as protagonists. However, when the poor are viewed as passive incapable recipients of actions from the state, the programs and policies implemented tend to yield practices and results which are questionable or inefficient in nature.